The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0100-29452011000500085
|View full text |Cite
|
Sign up to set email alerts
|

Melhoria da qualidade de uva 'Bordô' para produção de vinho e suco de uva

Abstract: Visando à produção de vinho e suco de uva de melhor qualidade, o objetivo desta pesquisa foi aumentar a relação de sólidos solúveis totais/acidez total titulável (SST/ATT), conhecida como flavor, da uva 'Bordô', com o uso de reguladores vegetais e avaliar os efeitos destes produtos nas demais características físico-químicas dos frutos. O trabalho foi realizado durante duas safras, 2009/2010 e 2010/2011, em Bocaiuva do Sul-PR. As variáveis físicas analisadas foram: comprimento e largura dos cachos; diâmetro das… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
2
3
0
6
Order By: Relevance
“…These values were similar to those reported by Ribeiro (2013) for the region of Jundiaí-SP (157.7g). On the other hand, Bordô cultivar showed the lowest bunch fresh weight value (93.3g) similar to that obtained by Chiarotti et al (2011) for Bocaiuva do Sul-PR. For Isabel Precoce, Isabel and Concord cultivars, intermediate bunch fresh weight values were obtained, ranging from 126 to 148.4g.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These values were similar to those reported by Ribeiro (2013) for the region of Jundiaí-SP (157.7g). On the other hand, Bordô cultivar showed the lowest bunch fresh weight value (93.3g) similar to that obtained by Chiarotti et al (2011) for Bocaiuva do Sul-PR. For Isabel Precoce, Isabel and Concord cultivars, intermediate bunch fresh weight values were obtained, ranging from 126 to 148.4g.…”
Section: Resultssupporting
confidence: 78%
“…Values obtained for Isabel cultivar in VSP training system were higher than those observed in northern Paraná (ASSIS et al, 2011), Serra Gaúcha (RIZZON and MIELE, 2006);Caldas (PEREIRA et al, 2008) and Muzambinho, in Minas Gerais (APARECIDO et al, 2017). Bordô cultivar showed the lowest soluble solids content (15.1 °Brix), similar to values reported by Chiarotti (2011) for Bocaiuva do Sul-RS and lower than those observed by Pereira et al (2008) in Caldas-MG. BRS Violeta and Concord cultivars presented intermediate values, respectively 17.2 and 16.9 °Brix, higher than those observed for 'Concord' cultivated in Eldorado do Sul (ANZANELLO et al 2008) and Caldas-MG (PEREIRA et al al., 2008). For BRS Violeta cultivar, Aparecido et al (2017) observed, even during the winter season, total soluble solids content of 15.7 °Brix, while Silva et al (2017) reported value of 18.4 °Brix for 'BRS Violeta' in the region of Jundiaí-SP.…”
Section: Soluble Solids Content (Ss) -supporting
confidence: 85%
“…Para a variável sólidos solúveis, observaram-se valores superiores para a variedade Isabel Precoce nas duas safras avaliadas, sendo que, na safra 2015/2016, os valores de sólidos solúveis da variedade Isabel Precoce foram similares aos da variedade Bordô, apresentando 15,6 e 15,3 ºBrix, respectivamente. De acordo com Chiariotti et al (2011), a uva 'Bordô' produzida nas Regiões Sul e Sudeste apresentam deficiência na maturação, prejudicando o teor de sólidos solúveis das bagas, refletindo no suco, que exige um limite mínimo de 14°Brix (BRASIL, 2018). *Médias seguidas da mesma letra, na linha, não diferem entre si pelo teste Tukey a 5% de probabilidade de erro.…”
Section: Safra 2016/2017unclassified
“…Positive effects of GA 3 were observed in 'Sauvignon Blanc', 'Riesling', 'Lemberge' and 'Kadarka' cultivars, in the early ripening of grapes and in the high values of soluble solids, which is an important factor for the production of quality grapes and wines (TESZLAK et al, 2013). The application of GA 3 also promoted the increase of fresh and dry mass of 'Fujiminori' grapes (JUN et al, 2001) and improved the quality of 'Bordô' grapes, causing an increase in soluble solids content and a reduction in titratable acidity (CHIAROTTI et al, 2011). In 'Niagara' the application of GA 3 promotes the increase of berries mass, rachis mass and berry diameter (GUERIOS et al, 2016).…”
Section: Introductionmentioning
confidence: 99%